مساهمة التحقيق المحاسبي في دعم الرقابة الجبائية - زين, عبد المالك (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة الى معرفة مدى مساهمة التحقيق المحاسبي في دعم الرقابة الجبائية بإعتباره أداة من الأدوات الفعالة له، والذي من خلاله يتم اكتشاف الأخطاء والتجاوزات المرتكبة من طرف المكلفين بالتصريحات الجبائية وتبليغها لهم للقيام بالتعديلات اللازمة، وهذا لغرض حماية أهم الموارد المالية للخزينة العمومية. ولإسقاط الجانب النظري على الواقع الجبائي، تم القيام بدراسة حالة لتحقيق محاسبي لملف جبائي تابع للمديرية الولائية للضرائب بخنشلة حيث لاحظنا هناك فوارق في الأساس الخاضع لهذا الملف تم اكتشافها من خلال هذا التحقيق، وتم تبليغها للمكلف للقيام بالتعديلات اللازمة. This study aims at knowing the extent to which the accounting investigation contributes to supporting fiscal control as one of its effective tools. Through these tools, errors and abuses committed by those charged with tax declarations are discovered and communicated and therefore to make the necessary adjustments for the purpose of protecting the most important financial resources of the public treasury. In order to drop the theoretical aspect on the tax reality, a case study was carried out for an accounting investigation of a tax file in the tax directorate of Khenchela. We have noticed differences in the core subject to this file that were discovered through this investigation. After that, they were reported to the taxpayer to make the necessary adjustments
The contribution of the accounting investigation to support the fiscal control Case study of the state tax directorate, Khenchela
مقال
Keywords: التحقيق المحاسبيM42 ; الرقابة الجبائية H21 ; التصريحات الجبائية H26